Fact and fiction in economics : models, realism and social construction - Mäki, Uskali (Cambridge University Press, 2002)
Bringing together some of the leading figures in the methodology and philosophy of economics, this collection provides a thoughtful and balanced overview of the current state of debate about the nature and limits of economic knowledge.